2013
DOI: 10.1016/j.aju.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrolithotomy in the supine position: Safety and outcomes in a single-centre experience

Abstract: ObjectivesTo assess the feasibility of performing percutaneous nephrolithotomy (PCNL) with the patient supine. Although PCNL with the patient prone is the standard technique for treating large (>2 cm) renal stones including staghorn stones, we evaluated the safety and efficacy of supine PCNL for managing large renal stones, with special attention to evaluating the complications.Patients and methodIn a prospective study between January 2010 and December 2011, 54 patients with large and staghorn renal stones und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…8,14 Nour et al in his study found that three patients out of 54 renal unit undergoing PCNL in supine position needed an auxiliary endoscopic procedure under anaesthesia. 15 We have seen that two patients in each group of supine and prone PCNL further require second relook PCNL.…”
Section: Discussionmentioning
confidence: 87%
“…8,14 Nour et al in his study found that three patients out of 54 renal unit undergoing PCNL in supine position needed an auxiliary endoscopic procedure under anaesthesia. 15 We have seen that two patients in each group of supine and prone PCNL further require second relook PCNL.…”
Section: Discussionmentioning
confidence: 87%
“…Only the modified dorsal lithotomy position was a statistically significant predictor of ultrasound tract dilatation. While some have demonstrated that fluoroscopic access is feasible and safe in the supine position, our practice is to use ultrasound or simultaneous ureteroscopic visualization to guide tract access and dilatation when in this position. This particular association is most likely a reflection of practice pattern and illustrates the utility of ultrasound and direct‐vision tract dilatation when the patient is supine.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13] In the supine position, the risk of perforation of the colon (0.5%) is lower because the intestine floats freely in the abdomen away from the kidney. 14 Compared with single access, multiple access entails an increased risk of bleeding and complications, including a detrimental effect on renal function. 15 The digital insertion and dissection technique does not cause problems for the movement of the access sheath or leakage of saline solution with its instillation during the procedure, nor is bleeding modified.…”
Section: Discussionmentioning
confidence: 99%